Development of basic movement learning models of the concept of play and games modification elementary school level - Ari Wibowo Kurniawan; Yulingga Nanda Hanief (UIR Press, 2022)
The limited facilities for physical education (PE) teachers cause learning less varied patterns, so it impacts the development of students' basic movements. This study aims to develop a learning model using the play and games modification concept to facilitate the needs of basic movement at the elementary school level. This research is development research with five stages, namely; (1) need assessment, (2) product design selection, (3) product development, (4) implementation, and (5) product evaluation. This research produces a product and investigates the efficiency of that product to facilitate elementary school students’ basic movement fulfillment. The subjects in this study are the physical education teachers from Malang regency, Lumajang Regency, Malang City, Lamongan Regency, Blitar City, and Kediri Regency, East Java, Indonesia. From the six regions, 10 schools are involved as subjects, each of which included 25 teachers.The research results suggest that this learning model with play and games modification concept can be used and facilitate the attainment of elementary school students’ basic movement. Thus, the learning model can be categorized as feasible and can promote the fulfillment of the basic movement needs at the elementary school level. The results have significance for elementary school students. The findings can assist teachers in providing facilities for the basic movement needs of children at the elementary school level.